Shaping the Profession: Australian Counselling Educators' Perspectives on Professional Identity, Values, and Education - Nathan Beel; Sharyn Taylor; Christine Chinchen (Psychotherapy and Counselling Journal of Australia)
Counselling educators play a major role in shaping the profession by socialising the future generations of counsellors; however, they have been subject to little research. This study explores the views and perceptions of Australian counselling educators about the counselling profession’s values, identity, and educational practices. For this qualitative study, we interviewed eight counselling educators and applied thematic analysis to develop themes. Three primary themes were developed, namely, the emphasis on the person of the therapist, the importance of quality counselling education, and the distinctiveness and credibility of the counselling profession. The counselling educators expressed core values in alignment with contemporary Australian counselling scholarship, while also noting potential threats to counsellor education and, downstream, the reputation of the profession. These threats included training institution agendas that undermined educator attempts to maintain the quality of counsellor preparation. Given the threats to quality arising from the training institutions’ own conflicts of interest, professional bodies may need to consider additional gatekeeping mechanisms for graduates entering the profession.